PODILLIAN FOLKLORE IN SCIENTIFIC STUDIES - Домилівська, Людмила; Коломицева, Марія; Марчун, Оксана (SWorldJournal, 2026)
The article highlights the main stages and directions of studying the folklore of Podillya in domestic and foreign scientific studies. The work of Ukrainian folklorists, ethnographers and ethnomusicologists of the late 19th - early 21st centuries is analy